Evaluation of Land Suitability of The Post-Mine Area for Settlement in The Kuranji Region of Padang City - Chani, Anwar; Andayono, Totoh (Universitas Negeri Padang, 2024)
The increase in population in Padang City is related to the many needs that must be met by the community such as housing or settlement needs. The availability of land that meets the criteria to be used as a settlement location guarantees a decent life for each community. This research aims to evaluate the land suitability of post-mining areas for settlements in the Kuranji area of Padang City. Data collection is done by analyzing the parameters used in determining the ideal settlement area, namely, slope level map, soil type map, erosion hazard, soil texture, flood hazard, and soil carrying capacity. The data that has been obtained is analyzed using the scoring or weighting method to determine the level of land suitability. Based on the calculations and analysis carried out on the evaluation of land suitability for settlements in the Gunung Sarik area, it can be concluded that the post-mining area in the Gunung Sarik area is suitable for settlements with a land suitability level value of 57 which with a land suitability level value of 58.7 - 37.4 is appropriate with details of 6 physical parameters that are met, namely, the level of slope 15.76%; Alluvial soil type, erosion hazard 348.83 tons/day/year, never flooded, fine soil texture (Clay), and has good soil bearing capacity (165 kg/cm 2 ).